2019
DOI: 10.20944/preprints201908.0255.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macrodebris and Microplastics Pollution in Nigeria: First Report on Abundance, Distribution and Composition

Abstract: The abundance, distribution and composition of marine debris (> 5 cm) and small microplastics (11 μm) from five rivers in South Eastern, Nigeria was investigated. This study provided the first assessment of the type and quantity of marine litter and microplastics in Nigeria. A total of 3487 macrodebris items/m2 were counted with the following distribution; plastics (59 %) > metal (10 %) > cloth (7 %), paper /cardboard (7 %), rubber (7 %) > glass/ceramics (5 %), medical and ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
1
22
0
5
Order By: Relevance
“…Similarly, a study of Cross River, Qua Iboe River and Jaja Creek in Akwa Ibom, Nigeria for suspended marine litter also reported high quantity of plastic (> 5000 kg/ m 2 ) compared to other waste (can, foil etc < 1000 kg/m 2 ) [19]. Reports have shown that Macroplastics correlated strongly with microplastics indicating that wherever there is high abundance of macroplastics, there will be a corresponding high abundance of microplastics in that area [13,20]. Therefore, quantifying the abundance of microplastics and identifying their major sources in Nigerian environments is important to understand the potentially adverse impacts of microplastics to ecological systems in the country.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Similarly, a study of Cross River, Qua Iboe River and Jaja Creek in Akwa Ibom, Nigeria for suspended marine litter also reported high quantity of plastic (> 5000 kg/ m 2 ) compared to other waste (can, foil etc < 1000 kg/m 2 ) [19]. Reports have shown that Macroplastics correlated strongly with microplastics indicating that wherever there is high abundance of macroplastics, there will be a corresponding high abundance of microplastics in that area [13,20]. Therefore, quantifying the abundance of microplastics and identifying their major sources in Nigerian environments is important to understand the potentially adverse impacts of microplastics to ecological systems in the country.…”
Section: Introductionmentioning
confidence: 88%
“…Taiwan), Australia, America (California, certain areas in Argentina, Brazil, Chile, and Colombia) while some African countries (Kenya, Mali, Cameroon, Tanzania, Uganda, Ethiopia, Malawi, Morocco, South Africa, Rwanda, and Botswana) have also banned plastic bags [11], though in principle but not in practice. In Nigeria, the problem of plastic pollution still persist and potentially on the increase, even though there are existing laws that may tackle these problems [12], but are not implemented or are poorly enforced [13]. Plastic industry in Nigeria is receiving massive investment and thus experiencing significant growth.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations